KOMODIFIKASI KEUNIKAN KAMPUNG ADAT CIREUNDEU SEBAGAI OBJEK WISATA BUDAYA - Nunung Sanusi; Adi Permana Sidik (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
ABSTRACT Indonesia has a diversity of ethnicities, cultures, languages ​​and religions that are spread throughout the country from Sabang to Morocco is a gift that we must maintain as a nation that has a philosophical foundation of Bhineka Tunggal Ika. If we ignore the cultural diversity we have, then that potential will be lost and have no meaning at all. One of them is the existence of traditional villages that still maintain the traditional values ​​of their ancestors. Cireundeu Traditional Village is one of the traditional villages in West Java that attracts many people. The uniqueness of the traditional village and the lifestyle of the people make tourists visit, so there are business actors who sell tour packages and produce processed cassava in the Cireundeu traditional village. This study seeks to answer (1) the form of commodification of cultural uniqueness in the traditional village of Cireundeu as a cultural tourism object, (2) the factors that influence commodification, and (3) the extent to which the impact of this commodification takes place on the indigenous people of Cireundeu. This study uses a qualitative approach and descriptive analysis, as well as the theory of commodification. Collecting data by literature study, observation, interviews, and documentation.